2015
DOI: 10.1038/sc.2015.57
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of diffusion tensor imaging and phase-contrast MR with clinical parameters of cervical spinal cord injuries

Abstract: Study design: This is a cross-sectional study. Objectives: The goal of this study was to characterize the diffusion properties across segments of the spinal cord and peak cerebrospinal fluid (CSF) velocities in the stenotic spinal canal, and to determine the correlation between these properties and clinical and electrophysiological parameters in patients with cervical spinal cord injury (SCI). Setting: This study was conducted in the University teaching hospital. Methods: The study involved 17 patients with ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…The significant changes in FA AL and RD AL observed in individuals with chronic SCI (Table 3) are also in agreement with the previous findings. Similarly, the observed significant correlation between functional impairment and the values of the DTI indices is in accordance with previous studies [11, 14, 17, 23], where lower FA and higher AD and RD values are reported to be correlated with worse ISNCSCI scores.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The significant changes in FA AL and RD AL observed in individuals with chronic SCI (Table 3) are also in agreement with the previous findings. Similarly, the observed significant correlation between functional impairment and the values of the DTI indices is in accordance with previous studies [11, 14, 17, 23], where lower FA and higher AD and RD values are reported to be correlated with worse ISNCSCI scores.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, we observed that compared to FA AL , FA IRRI showed stronger correlation with ISNCSCI-tot, which is in accordance with a previous study [17] – indicating that subject-specific regional measures of FA, and in particular, those measured from IRRI-region, may be more specific to impairment. A similar trend of stronger correlations between ISNCSCI-tot and other IRRI-region DTI indices, specifically RD IRRI and AD IRRI , was also observed (Table 4).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Current clinical standards rely on functional testing, such as American Spinal Injury Association scoring for characterizing injury, but are often unreliable for predicting long‐term functional outcomes due to changes in score over time within some patients . Clinical magnetic resonance imaging (MRI), such as T 2 ‐weighted imaging, has aided SCI assessment, but similarly does not reliably predict long‐term functional outcomes due to the lack of specificity to axonal damage, the strongest pathological correlate of long‐term functional outcome following SCI . Thus, techniques such as diffusion‐weighted imaging (DWI), and diffusion tensor imaging (DTI) in particular, have garnered considerable interest as noninvasive biomarkers of SCI due to their sensitivity to microscopic axonal damage …”
mentioning
confidence: 99%